Method for measuring the dielectric constant distribution of resin moldings
The method employs X-ray CT to non-destructively measure the dielectric constant distribution in resin molded bodies, addressing the limitations of existing destructive methods and ensuring accurate dielectric constant control and insulation reliability.
Patent Information
- Application Number
- JP2021123340
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-07-28
AI Technical Summary
Existing methods for verifying the dielectric constant distribution in resin molded bodies, such as insulating spacers, are destructive and lack the capability for non-destructive, automatic, and rapid assessment.
A method utilizing X-ray Computed Tomography (CT) to acquire images of resin molded bodies, derive the relationship between dielectric constant and brightness from standard samples, and calculate the relative permittivity distribution non-destructively.
Enables non-destructive, automatic, and rapid determination of relative permittivity distribution in resin molded bodies, ensuring accurate dielectric constant inclination and resistance to dielectric breakdown.
Smart Images

Figure 0007654221000007 
Figure 0007654221000008 
Figure 0007654221000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for measuring the relative dielectric constant distribution of a resin molded body, and more particularly to a method for obtaining the relative dielectric constant distribution of a resin molded body in a non-destructive manner. [Background technology]
[0002] A gas-insulated switchgear has a structure in which a high-voltage conductor is arranged in a metal sealed container. In such a gas-insulated switchgear, a solid insulator called an insulating spacer is used to fix the high-voltage conductor at a predetermined position in the sealed container. In a conventionally commonly used cone-shaped insulating spacer, a high-voltage conductor is provided in the center, and an insulating spacer is provided to support the high-voltage conductor. A metal flange is attached to the periphery of the insulating spacer, and the insulating spacer is sandwiched between the connecting flanges of the sealed container by the metal flange and fixed to the sealed container. In addition to the above, insulating spacers used in gas-insulated switchgear have various shapes and structures, such as a disk-shaped one, one with axially symmetrical irregularities, and one through which three high-voltage conductors pass.
[0003] In recent years, there has been a demand for greater economic efficiency, and there is a demand for more compact gas-insulated switchgear. In conventional insulating spacers, the concentration of electric fields in the gas space caused by the difference in dielectric constant between the insulating gas, which is mainly composed of SF6, and solid insulating materials, as well as the need to control conductive foreign matter, have hindered the compactification of the spacer. In order to achieve this, functionally graded materials (ε-FGMs), in which the dielectric constant of the cone-shaped insulating spacer is changed in the radial direction, have been studied. Among these, a cone-shaped insulating spacer composed of multiple insulating resin layers with different relative dielectric constants is known (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-327580 A Summary of the Invention [Problem to be solved by the invention]
[0005] When manufacturing an insulating spacer with a graded dielectric constant aimed at reducing the electric field strength, it is necessary to laminate multiple resin layers with different dielectric constants as in Patent Document 1, or to form a molded body in which the dielectric constant changes continuously without forming a resin layer. In this case, the dielectric constant is designed to be adjusted by the type and amount of filler contained in the resin layer, and the insulating spacer is manufactured by pouring the resin prepared according to the design into a mold by vacuum casting or pressure gelation method and then heating and curing.
[0006] The insulating spacer obtained after heat curing needs to be inspected for quality before shipping. However, the only method available to date for checking whether the dielectric constant is as designed was a destructive method, such as cutting the manufactured insulating spacer.
[0007] In electronic devices that include not only insulating spacers but also resin molded articles that require the design of the dielectric constant distribution, a method is required to confirm the dielectric constant distribution of the resin molded article in a non-destructive manner. [Means for solving the problem]
[0008] As a result of extensive investigations, the inventors of the present invention came up with the idea of obtaining the relative dielectric constant distribution of a resin molded body based on the brightness obtained from an X-ray CT (Computed Tomography) image, and completed the present invention.
[0009] That is, according to one embodiment, the present invention provides a method for measuring a dielectric constant distribution of a resin molding, comprising the steps of: (a) obtaining an X-ray CT image of a resin molded body; (b) obtaining brightness from the X-ray CT image obtained in step (a); (c) deriving a relational expression between the dielectric constant and luminance of the resin molded body based on a relationship between the dielectric constant and luminance previously obtained from a sample having a known dielectric constant; (d) calculating the relative dielectric constant of the resin molding from the luminance obtained in the step (b) and the relational expression derived in the step (c); Includes.
[0010] In the method for measuring a dielectric constant distribution of a resin molded body, the step (c) is
number
[0011] In the method for measuring the dielectric constant distribution of a resin molded body, it is preferable that the relationship between the dielectric constant and the luminance, which is obtained in advance from a sample whose dielectric constant is known, is expressed by an exponential curve showing the relationship between the dielectric constant and the luminance.
[0012] In the method for measuring a dielectric constant distribution of a resin molded body, it is preferable that the resin molded body is a cone-shaped insulating spacer.
[0013] In the method for measuring the dielectric constant distribution of a resin molding, it is preferable that the cone-shaped insulating spacer is a cone-shaped insulating spacer that supports a central conductor, is arranged around the central conductor, and includes two or more insulating resin layers along the axial direction of the central conductor.
[0014] In the method for measuring the dielectric constant distribution of a resin molded body, it is preferable to obtain the dielectric constant distribution along a straight line from a central conductor toward an edge portion on an X-ray CT image of the cone-shaped insulating spacer.
[0015] According to yet another embodiment, the present invention provides a method for manufacturing a cone-shaped insulating spacer, comprising the steps of: (A) a step of molding a cone-shaped insulating spacer having a resin molded body with a gradient dielectric constant by a vacuum casting or pressure gelation method; (B) measuring and inspecting the dielectric constant distribution of the obtained resin molding by any one of the dielectric constant distribution measuring methods described above; Equipped with. Effect of the Invention
[0016] According to the method for measuring the dielectric constant distribution of a resin molded body of the present invention, the dielectric constant distribution of the resin molded body can be obtained non-destructively, automatically, and in a short time by using an X-ray CT image. This makes it possible to obtain a resin molded body having a desired dielectric constant gradient, in particular a cone-shaped insulating spacer having a desired dielectric constant gradient and dielectric breakdown resistance. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a conceptual cross-sectional view illustrating a cone-shaped insulating spacer, which is an example of a resin molding to which a measuring method according to the present invention can be applied. [Diagram 2] FIG. 2 shows a three-dimensional X-ray CT image (left side) and a two-dimensional X-ray CT image (right side) of the cone-shaped insulating spacer shown in FIG. [Diagram 3] FIG. 3(a) is an example of a two-dimensional X-ray CT image of a standard sample used in the analysis, and FIG. 3(b) shows a histogram obtained from the entire circular standard sample in this two-dimensional X-ray CT image. [Figure 4] Figure 4 is a graph illustrating the master curve obtained by plotting the dielectric constant of a standard versus luminance, with error bars indicating the non-zero frequency region of the histogram. [Diagram 5] FIG. 5 shows a two-dimensional X-ray CT image (right side) of a cone-shaped insulating spacer according to an embodiment, and a graph (left side) showing the relative dielectric constant distribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. However, the present invention is not limited to the embodiment described below.
[0019] The present invention relates to a method for measuring the relative dielectric constant distribution of a resin molded body. The resin molded body to be measured in the present invention is not particularly limited, and may be any thermosetting resin, thermoplastic resin, or a combination thereof, and may have a conductor part in contact with the resin molded body. The resin molded body may typically be a part of an electronic device together with a conductor member, and may be a gradient dielectric material in which the relative dielectric constant may be different in parts inside the resin molded body. Furthermore, it is preferable that the resin molded body to be measured is a gradient dielectric material including two or more parts with known relative dielectric constants. Examples of the resin molded body may be, but are not limited to, the resin part of a cone-shaped insulating spacer, a columnar insulating porcelain, a sealing material for a semiconductor device, a molded resin for a molded transformer, a coating resin for a vacuum valve, and a coating resin for a high-voltage conductor.
[0020] The following description will be given taking a cone-shaped insulating spacer as an example of a resin molded article to be measured. However, the present invention is not limited to the method for measuring the relative dielectric constant distribution of a cone-shaped insulating spacer. FIG. 1 is a conceptual cross-sectional view for explaining a cone-shaped insulating spacer. Referring to FIG. 1, the cone-shaped insulating spacer is mainly composed of a central conductor 10, an insulating resin part 12 composed of five insulating resin layers 12a, 12b, 12c, 12d, and 12e, and a metal flange 11 on the periphery. The metal flange 11 is sandwiched between two sheaths 13 and fixed by a fixture 14.
[0021] The insulating resin part 12 supports the central conductor 10 and is provided around the central conductor 10. One surface along the axial direction A of the central conductor 1 is formed as a convex surface C, and the other surface is formed as a concave surface R. Five insulating resin layers 12a, 12b, 12c, 12d, and 12e are laminated from the convex surface C toward the concave surface R, and it is preferable that multiple interfaces of each layer are formed approximately parallel to each other.
[0022] The number of insulating resin layers stacked in the illustrated cone-shaped insulating spacer may be 2 or more, and is not limited to the illustrated embodiment. It is preferably 3 or more, more preferably 6 or more, for example, about 20 or less. The thicknesses of the insulating resin layers may be the same or different, and is not limited to the illustrated embodiment.
[0023] According to the dielectric constant distribution measuring method of the embodiment of the present invention, it is possible to obtain the dielectric constant distribution at any point in a resin molding exemplified by a cone-shaped insulating spacer shown in FIG. 1. For example, it is possible to obtain the dielectric constant distribution along a straight line set on a two-dimensional X-ray CT image of the resin molding, and in FIG. 1, it is possible to obtain the dielectric constant distribution along a straight line drawn from the central conductor 10 of the cone-shaped insulating spacer toward the flange 11. Also, while FIG. 1 is a diagram showing one cross section passing through the axis A of the cone-shaped insulating spacer, any straight line can be set for other cross sections passing through the axis A or any other cross sections, and the dielectric constant distribution can be obtained. Then, it is possible to obtain the dielectric constant distribution of substantially the entire resin molding having a three-dimensional cone-shaped structure.
[0024] The method for measuring the relative dielectric constant distribution of a resin molding includes the following steps. (a) A step of obtaining an X-ray CT image of a resin molded body (b) obtaining brightness from the X-ray CT image obtained in the step (a); (c) deriving a relational expression between the dielectric constant and luminance of the resin molded body based on a relationship between the dielectric constant and luminance previously obtained from a sample having a known dielectric constant; (d) calculating the relative dielectric constant of the resin molded body from the luminance obtained in the step (b) and the relational expression derived in the step (c);
[0025] (a) A process for acquiring an X-ray CT image In step (a), an X-ray CT image of the resin molded body is obtained. The X-ray CT image can be obtained using a commercially available industrial X-ray CT device. The X-ray CT device may be any device capable of obtaining an X-ray CT image of the resin molded body, and may typically be a device equipped with an X-ray tube and a detector, and further equipped with a stage on which an imaged object is placed. The detector may be a planar detector or a linear detector. The imaging conditions of the X-ray CT device can be appropriately set to suit the imaged object. However, the tube voltage, tube current, and resolution are the same when imaging the resin molded body and when imaging a standard sample described later. This is because there is a risk that the brightness will change even for the same sample if the intensity of the X-ray changes. In addition, in the case of a structure in which a metal member is close to the resin molded body to be imaged, it is preferable to place a metal filter that cuts soft X-rays on the X-ray source when imaging. This is to reduce noise called metal artifacts.
[0026] The upper left image in Fig. 2 is a three-dimensional X-ray CT image of the cone-shaped insulating spacer shown in Fig. 1, and the upper right image is an example of a two-dimensional X-ray CT image of a cross section passing through the axis A of the cone-shaped insulating spacer shown in Fig. 1. In step (a), two-dimensional and / or three-dimensional X-ray CT images can be acquired for multiple cross sections as necessary. For example, for the cone-shaped insulating spacer shown in Fig. 1, four X-ray CT images of a cross section passing through the axis A may be acquired every 90°, or even more images may be acquired every 45° or every 30°.
[0027] (b) The process of obtaining brightness In step (b), the X-ray CT image acquired in step (a) is analyzed to obtain the brightness. More specifically, the X-ray CT image is analyzed using image analysis software and displayed, for example, in 8-bit grayscale to obtain a brightness value. The brightness is obtained as a group of numerical data corresponding to each part on the image according to the resolution of the X-ray CT device used. By specifying a specific part on the image, the numerical brightness data of the required part can be obtained from this group of numerical data.
[0028] (c) A process of deriving a relational equation between the relative dielectric constant and luminance of the resin molded body. In step (c), the relational expression between the dielectric constant and brightness of the resin molded body to be measured is derived. For the derivation, the relation between the dielectric constant and brightness previously obtained from a sample with a known dielectric constant is used. In this step, first, the derivation of the relation between the dielectric constant and brightness using a standard sample with a known dielectric constant will be described. The standard sample is used to create a master curve for the purpose of deriving the relational expression between the dielectric constant and brightness of the resin molded body to be measured, and refers to a combination of two or more separate samples with different dielectric constants. It is preferable to create one master curve for each combination of two or more inorganic fillers in the resin constituting the standard sample. When the combination of inorganic fillers is different, for example, even if the standard sample has the same dielectric constant of 12, the brightness is different when the inorganic fillers that are the constituents are A and B and the value of the dielectric constant is A:B=10:3 and when the inorganic fillers that are the constituents are A and C and the value of the dielectric constant is A:C=10:5. This is because the density of the inorganic fillers is different, and therefore the absorption coefficient of X-rays is different. Therefore, when the combination of inorganic fillers is different, it is necessary to retake the master curve.
[0029] Therefore, the standard sample is prepared from the same material as the resin composition constituting the resin molded product to be measured, and the base resin and the filler are the same type, and the content of the filler can be changed to obtain a sample with a different dielectric constant. The shape and thickness of the standard sample are not particularly limited, but the standard sample must be a uniformly formed molded product with substantially no distribution (bias) of the dielectric constant. The left column of Figure 2 shows three-dimensional X-ray CT images of eight disk samples that can be used as standard samples, and the right column shows two-dimensional X-ray CT images of the cross section through the diameter of each disk. The known dielectric constant of the disk is shown next to the two-dimensional X-ray CT image of each disk.
[0030] The more standard samples there are, the more accurate the relational equation can be derived, but it is preferable to obtain the brightness for at least three standard samples. In addition, it is preferable that the standard samples include at least a sample with a dielectric constant of about 0.1 larger than the lowest dielectric constant predicted for the resin molded body to be measured and a sample with a dielectric constant of about 1.0 larger than the highest dielectric constant. The part with the lowest dielectric constant is usually composed of a resin and one type of inorganic filler. The X-ray absorption coefficient is different between a sample prepared using a resin and one type of inorganic filler and a sample prepared using a resin and two types of inorganic fillers. Therefore, even if the dielectric constant is the same, the brightness tends to differ. Therefore, it is better for the smaller dielectric constant to be slightly larger than the lowest dielectric constant as a standard sample containing two types of inorganic fillers.
[0031] For each standard sample, the X-ray CT two-dimensional image is analyzed by image analysis software in the same manner as in step (b), and displayed, for example, in 8-bit grayscale. Then, a portion in the image for which the brightness is to be obtained is selected, and a histogram is output. The portion to be selected may be substantially the entire image of the standard sample, or may be a portion, provided that it is consistent between the standard samples. The mode of the obtained histogram can be used as the brightness of the standard sample. FIG. 3(a) is an example of an X-ray CT two-dimensional image of a standard sample used in the analysis, and FIG. 3(b) is a histogram obtained from the entire standard sample that forms a circular shape in the X-ray CT two-dimensional image of FIG. 3(a). From FIG. 3(b), the mode of this histogram can be read as 188. This operation is performed for multiple standard samples to obtain the brightness of all the standard samples. It is not necessary to adopt the mode of the histogram as the brightness of the standard sample from the brightness data group of the standard sample, and it can be appropriately determined from values such as the average value and median value.
[0032] Based on the relationship between the dielectric constant and the luminance obtained for multiple standard samples, the dielectric constant (x) is plotted on the horizontal axis and the luminance (I) on the vertical axis. Next, the relationship between the dielectric constant and the luminance is made into an exponential function as shown in the following formula (0), and an approximation curve (master curve) is created by fitting the plot.
number
[0033] Step (c) may include a sub-step of deriving this master curve, or the master curve may be derived in advance.
[0034] Next, a relational expression between the dielectric constant and brightness of the resin molded body, which is the measurement target sample, is derived. First, brightness at at least two points with known dielectric constants is extracted from the brightness value already obtained in step (b). Here, the points with "known dielectric constant" refer to points in the resin molded body where the designed dielectric constant is estimated to be realized. The two points preferably include at least a sample with a dielectric constant of about 0.1 larger than the minimum dielectric constant predicted for the resin molded body to be measured and a sample with a dielectric constant of about 1.0 larger than the maximum dielectric constant. This allows at least two sets of dielectric constant and brightness values to be obtained.
[0035] The relation between the relative dielectric constant and luminance of the resin molded body, which is the measurement sample, is also expressed as the following formula (1): The value of α in formula (1) is the same as the value of α in formula (0).
number
[0036] (d) A step of calculating the relative dielectric constant of the resin molded body If the relational expression (1) is obtained, the luminance of the desired portion obtained in step (b) is applied to the relational expression (1) obtained in step (c) to obtain the dielectric constant of the desired portion. By performing the operation of this step (d) for a plurality of portions on the two-dimensional X-ray CT image, the distribution of the dielectric constant on the two-dimensional X-ray CT image can be obtained. In addition, by performing the operation of step (d) similarly for another two-dimensional X-ray CT image obtained for the same resin molded body, the distribution of the dielectric constant for yet another portion can be obtained, and by combining these, the distribution of the dielectric constant can be obtained for a desired portion of the resin molded body, which is a three-dimensional structure. In a preferred embodiment, a straight line is drawn at a desired portion on the two-dimensional X-ray CT image of the resin molded body, and a line analysis is performed along the straight line, thereby obtaining the distribution of the dielectric constant along the desired straight line portion. It is preferable to perform the line analysis along a portion of the resin molded body where it is estimated that a resin designed and manufactured to change the dielectric constant is present. In addition, the relationship between the pixel position and the dielectric constant on the two-dimensional X-ray CT image can be used to calculate the relationship between the distance from a specific portion of the resin molding and the dielectric constant. More specifically, in the case where the resin molding is a cone-shaped insulating spacer as shown in Fig. 1, if the distance along the axis A from the tip of the convex surface C is defined as the height, the relationship between the height of the resin molding and the dielectric constant can be calculated using the relationship between the pixel position and the dielectric constant.
[0037] [Second embodiment: Manufacturing method of cone-shaped insulating spacer] According to a second embodiment, the present invention provides a method for manufacturing a cone-shaped insulating spacer, which includes the following steps. (A) a step of molding a cone-shaped insulating spacer having a resin molded body with a gradient dielectric constant by a vacuum casting or pressure gelation method; (B) A step of measuring and inspecting the relative dielectric constant distribution of the obtained resin molded body by the method according to any one of claims 1 to 5.
[0038] In step (A), a cone-shaped insulating spacer having a resin molding with a gradient of relative dielectric constant to suit the product characteristics is designed and manufactured. The cone-shaped insulating spacer may be a gradient dielectric constant material in which multiple layers are laminated as shown in Figure 1. For such a cone-shaped insulating spacer, the gradient dielectric constant material can be designed by a conventionally known method.
[0039] Next, the cone-shaped insulating spacer is molded based on the design. The following is an example of the manufacture of a cone-shaped insulating spacer having a plurality of laminated layers. The material of the insulating resin layer constituting the cone-shaped insulating spacer can be selected from the following options, for example.
[0040] The thermosetting resin may be, for example, an epoxy resin, a maleimide resin, a cyanate resin, or a mixture thereof. The thermosetting resin is preferably an epoxy resin. The epoxy resin preferably contains an epoxy resin base, a curing agent, and optionally a curing accelerator. The epoxy resin base may be an aliphatic epoxy, an alicyclic epoxy, or a mixture thereof. Examples of the aliphatic epoxy resin include, but are not limited to, bisphenol A type epoxy, bisphenol F type epoxy, bisphenol AD type epoxy, biphenyl type epoxy, cresol novolac type epoxy, and polyfunctional epoxy having three or more functional groups. These may be used alone or in a mixture of two or more types. Examples of the alicyclic epoxy resin include, but are not limited to, monofunctional epoxy, bifunctional epoxy, and polyfunctional epoxy having three or more functional groups. The alicyclic epoxy resin may also be used alone or in a mixture of two or more different alicyclic epoxy resins.
[0041] The thermosetting resin composition may contain a curing agent for the thermosetting resin as an optional component. The curing agent is not particularly limited as long as it reacts with the base material of the thermosetting resin and can be cured. For example, it is preferable to use an acid anhydride curing agent as a curing agent for the epoxy resin base material. Examples of the acid anhydride curing agent include aromatic acid anhydrides, specifically phthalic anhydride, pyromellitic anhydride, trimellitic anhydride, etc. Alternatively, cyclic aliphatic acid anhydrides, specifically tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, etc., or aliphatic acid anhydrides, specifically succinic anhydride, polyadipic anhydride, polysebacic anhydride, polyazelaic anhydride, etc., but are not particularly limited. The amount of curing agent added may be the amount necessary for curing the base material, and although it varies depending on the type of base material and curing agent, it can be appropriately determined by a person skilled in the art.
[0042] The thermosetting resin composition may also contain a curing accelerator for the thermosetting resin as an optional component. As the curing accelerator, imidazole or a derivative thereof, a tertiary amine, a boric acid ester, a Lewis acid, an organic metal compound, an organic acid metal salt, etc. can be appropriately used, but is not particularly limited.
[0043] Furthermore, the thermosetting resin composition may contain optional additives to the extent that the properties of the composition are not impaired. Examples of additives include, but are not limited to, flame retardants, pigments for coloring the resin, and plasticizers and silicone elastomers for improving crack resistance.
[0044] The type and amount of the inorganic filler can be designed so that the dielectric constant of the thermosetting resin composition is a desired value, and the inorganic filler can be included in the resin. As the inorganic filler, an insulating inorganic filler can be used. As a filler for preparing a resin with a relatively low dielectric constant, an inorganic filler with a dielectric constant of less than 6 can be used. As a filler for preparing a resin with a relatively high dielectric constant, an inorganic filler with a dielectric constant of 6 or more, preferably 10 to 15 or more can be used. In this specification, an inorganic filler with a dielectric constant of less than 6 is referred to as a low dielectric constant filler, and an inorganic filler with a dielectric constant of 6 or more is referred to as a high dielectric constant filler.
[0045] Examples of materials that can be used as the low dielectric constant filler include, but are not limited to, silica, boron nitride, aluminum hydroxide, aluminum nitride, talc, clay, mica, and glass fiber. The shape of the low dielectric constant filler is not particularly limited, and may be spherical, plate-like, needle-like, angular, etc.
[0046] Compounds that can be used as high dielectric constant fillers include alumina (Al2O3), dolomite (CaMg(CO3)2), titanium(IV) oxide (TiO2, anatase type TiO2), barium titanate (BaTiO3), strontium titanate (SrTiO3), lead titanate (PbTiO3), etc. These have a perovskite type crystal structure with a composition formula represented as ABO3, where the A element is Ba, Pb, La, etc., and the B element is Ti, Zr, etc., but are not limited to these. Other examples include lead zirconate titanate (PZT), lead niobate (PbNb2O6), hafnium (IV) oxide (HfO2), tantalum pentoxide (Ta2O5), zirconium oxide (ZrO2), yttria (Y2O3), chromium oxide (Cr2O3), copper oxide (CuO), nickel oxide (NiO), lithium niobate (LiNbO3), silicon (Si), and diamond. The shape of the high dielectric constant filler is not particularly limited, and may be spherical, plate-like, needle-like, angular, or the like. The shape of the high dielectric constant filler may be the same as or different from the shape of the low dielectric constant filler.
[0047] The inorganic filler may be a first inorganic filler having a relatively small average particle diameter and a second inorganic filler having a relatively large average particle diameter. The first inorganic filler is preferably an inorganic filler having an average particle diameter of 0.1 to 100 μm. The second inorganic filler is preferably an inorganic filler having an average particle diameter of 1 to 500 nm. Here, the average particle diameter refers to a value measured by a laser diffraction method. However, the average particle diameter of the first inorganic filler is larger than the average particle diameter of the second inorganic filler. In this specification, a filler having an average particle diameter of 0.1 to 100 μm is also referred to as a microfiller. Also, a filler having an average particle diameter of 1 to 500 nm is also referred to as a nanofiller. The first inorganic filler is preferably a high dielectric constant filler, and the second inorganic filler may be a high dielectric constant filler or a low dielectric constant filler. Also, it is preferable that the compound species constituting the first inorganic filler and the compound species constituting the second inorganic filler are not the same.
[0048] Next, insulating resin layers having the designed specific dielectric constant are laminated to form a cone-shaped insulating spacer. More specifically, the method can be carried out by a step of preparing a thermosetting resin composition according to a designed composition, injecting the thermosetting resin compositions constituting the insulating resin layers into an injection mold in a specific lamination order, and heating and curing the injected and laminated thermosetting resin compositions.
[0049] The injection mold may be one that is convex downward in the vertical direction and has a cavity in the center of the convex bottom surface in which a central conductor can be placed. The shape of the cavity can be appropriately designed to match the desired shape of the cone-shaped insulating spacer. The thermosetting resin compositions can be injected in the order starting from the thermosetting resin composition that constitutes the tip of the convex surface C. When thermosetting resin compositions with different compositions are injected into the injection mold, it is preferable to pour the upper layer resin after the resin injected first has permeated the injection mold.
[0050] A more detailed casting method may be, for example, the method disclosed in JP 2020-138486 A or JP 2020-138487 A, but is not limited to a specific casting method. In addition, the insulating spacer according to the present invention is not limited to the methods exemplified in this specification and can be manufactured by any method known for laminated cone-type insulating spacers, and can be manufactured by vacuum casting, pressure gelation method, vacuum pressure gelation method, etc.
[0051] After all the resins constituting the multiple insulating resin layers are injected, a heat curing process is performed. The conditions such as the heating temperature and time can be appropriately determined by a person skilled in the art so as to match the curing conditions of the thermosetting resin used. For example, when the thermosetting resin is an epoxy resin, it can be about 120 to 140°C and about 1 to 5 hours, but is not limited to specific conditions. In some cases, curing can be performed by two-stage heating. In addition, heating can be performed under atmospheric pressure or under reduced pressure.
[0052] After the above steps, optionally, a high voltage withstand test can be performed under conditions compatible with the rated voltage.
[0053] In step (B), the dielectric constant distribution of the insulating spacer obtained in step (A) can be measured to inspect whether it conforms to the product standard. The measurement of the dielectric constant distribution can be performed by the method described in detail in the first embodiment. Furthermore, based on the measurement method, a person skilled in the art can appropriately determine the inspection standard for whether the product can be shipped.
[0054] During actual operation, the rated voltage is applied for long periods of time, so the resin needs to have high insulating reliability. The cone-shaped insulating spacer manufactured by the manufacturing method according to the second embodiment of the present invention has been confirmed by testing to have a gradient dielectric constant according to the design and a high dielectric breakdown voltage, thereby achieving higher reliability. EXAMPLES
[0055] We designed and manufactured the cone-shaped insulating spacer shown in Figure 1. The number of layers of insulating resin was 5, and the flange was made of aluminum. The diameter of the cone-shaped insulating spacer including the tip of the flange was 60 mm, and the height was 21.7 mm. The base resin of each resin layer was epoxy resin, and the inorganic filler was silica (SiO2), barium titanate (BaTiO3), or both. The relative dielectric constant of each layer was changed by changing the compounding ratio of the inorganic filler.
[0056] To create the master curve, eight standard disk samples with a diameter of 60 mm and a thickness of 10 mm were prepared, each with a known dielectric constant. The standard samples were made using the same epoxy resin as the insulating spacer as the base resin, and the dielectric constant was changed by varying the amount of the same type of inorganic filler as the insulating spacer. The eight dielectric constants of the standard samples were as shown in Figure 2.
[0057] X-ray CT images of the cone-shaped insulating spacer and the standard specimen were taken. The X-ray CT equipment was GE A Phoenix V|tome|x C450 manufactured by SANYO was used. A rotating stage was placed between the X-ray generator and the X-ray detector, and a cone-shaped insulating spacer or a standard sample was placed on the rotating stage to obtain X-ray CT images. The tube voltage of the X-ray generator was 420 kV, the tube current was 400 μA, and the resolution of the X-ray detector (which changes with tube current / tube voltage) was 0.14669 mm. When taking images, a metal filter (Cu 1 mm + Sn 1 mm) that cuts soft X-rays was placed on the X-ray source to reduce noise.
[0058] A two-dimensional X-ray CT image of the part of the standard sample for which brightness was to be measured was output in JPEG format, and the output file was opened with the image analysis software Image J. Confirming that the opened image was 8-bit grayscale, the part for which brightness was to be calculated was selected. A histogram was output for the selected part, and the most frequent value of the histogram was taken as the brightness. The above operations were performed for the standard sample, with each line output for each relative dielectric constant. One of the histograms is shown in Figure 3(b). The relationship between the known relative dielectric constant I and brightness x was plotted on a graph, and fitting was performed with the graph creation software Igor to obtain a master curve. The master curve was calculated as follows. The master curve is shown in Figure 4.
number
[0059] The CT two-dimensional image of the cone-shaped insulating spacer was opened with the image analysis software Image j. The brightness of the part with a known dielectric constant on the CT two-dimensional image was obtained by Image j. In this embodiment, the dielectric constant of 12.7 near the tip of the convex part C, where the resin layer is thick and mixing with the resin of other layers is unlikely to occur, and the dielectric constant of 4 near the flange were known in terms of design and manufacturing. From the master curve of the standard sample, α = 0.147 in formula (1). The dielectric constant of 4 and the brightness of that part, and the dielectric constant of 12.7 and the brightness of that part were substituted into formula (1) to solve the simultaneous equations, and I0 and A were obtained. As a result, the relational equation (1) between the dielectric constant and brightness of the cone-shaped insulating spacer to be measured was obtained as follows.
number
[0060] The CT two-dimensional image of the cone-shaped insulating spacer was opened in Image j, and the layer was subjected to line analysis at 0.15 mm height intervals (corresponding to the resolution of X-ray CT) in the dielectric constant gradient area, and the brightness was read. The brightness was also read by line analysis at 90° intervals clockwise. The respective brightnesses were substituted into relational equation (1) to calculate the relative dielectric constant. The left panel of Figure 5 is a graph with the relative dielectric constant plotted on the horizontal axis and the height plotted on the vertical axis, and the right panel is an X-ray CT two-dimensional image. In the right panel, the area from the 0 mm line to the 21.7 mm line was analyzed in the direction of the arrow in the figure, and the brightness was read. "Non-destructive" refers to the relative dielectric constant (ε r ) is plotted. Destructive indicates the result of measuring another spacer that was destroyed. The sample height refers to the height when the insulating spacer is placed with the convex surface facing down and the concave surface facing up, and the tip of the convex surface is set to zero.
[0061] From Figure 5, ε r Although there is some variation around =12 that is thought to be due to noise (artifacts) caused by conductors (metal), ε r In the region where the relative dielectric constant is constant near = 4 and the region where the relative dielectric constant is inclined near the height of 10 mm, the ε r It was confirmed that the distribution was roughly consistent with the destructive measurement results. This example demonstrates that the relative dielectric constant distribution of a resin molding can be measured nondestructively using X-rays. [Industrial Applicability]
[0062] INDUSTRIAL APPLICABILITY The method for measuring the dielectric constant distribution of a resin molded body according to the present invention can be used in the manufacture of electrical equipment including a resin molded body, such as a gas-insulated switchgear. [Explanation of symbols]
[0063] 10 central conductor, 11 flange, 13a, 13b sheath, 14 fixing device 12a, 12b, 12c, 12d, 12e insulating resin layer, C convex, R concave
Claims
1. (a) acquiring an X-ray CT image of a resin molded body; (b) obtaining brightness from the X-ray CT image obtained in the step (a); (c) deriving a relational expression between the dielectric constant and luminance of the resin molded body based on a relationship between the dielectric constant and luminance previously obtained from a sample having a known dielectric constant; (d) calculating the relative dielectric constant of the resin molding from the luminance obtained in the step (b) and the relational expression derived in the step (c); the samples having known dielectric constants are prepared from materials having the same type of base resin and filler as the resin composition constituting the resin molded body to be measured, and the samples have different dielectric constants by changing the content of the filler.
2. The step (c) is a reaction of a compound represented by the following formula (1): [0010] (In the formula, I is the luminance, I 0 is the brightness when the X-ray passes through a space other than the sample, α is the attenuation coefficient of X-ray intensity, x is the relative dielectric constant, A is a constant. The method according to claim 1 , further comprising deriving a relational expression between the relative dielectric constant and luminance of the resin molded body, the relational expression being expressed by:
3. 3. The method according to claim 1, wherein the relationship between the dielectric constant and the luminance, which is previously obtained from a sample having a known dielectric constant, is expressed by an exponential curve showing the relationship between the dielectric constant and the luminance.
4. The method according to claim 1 , wherein the resin molding is a cone-shaped insulating spacer.
5. 5. The method according to claim 4, wherein the cone-shaped insulating spacer is a cone-shaped insulating spacer that supports a central conductor, is provided around the central conductor, and includes two or more insulating resin layers along an axial direction of the central conductor.
6. The method according to claim 5 , further comprising obtaining a relative dielectric constant distribution along a straight line from a central conductor toward an edge of the cone-shaped insulating spacer on an X-ray CT image of the cone-shaped insulating spacer.
7. (A) forming a cone-shaped insulating spacer having a resin molded body with a gradient dielectric constant by a vacuum casting or pressure gelation method; (B) measuring and inspecting the relative dielectric constant distribution of the obtained resin molded body by the method according to any one of claims 1 to 6; A method for manufacturing a cone-shaped insulating spacer comprising:
Citation Information
Patent Citations
Method for inspecting elastomer quake proof device having laminated rubber structure using x-ray ct
JP2001033402A
Multiphase state distribution measuring device and multiphase state distribution measuring method
JP2002214183A
Insulating spacer and gas-insulation equipment
JP2005327580A
Planar transmission-line permittivity sensor and calibration method for the characterization of liquids, powders and semisolid materials
US20160187402A1
Received-signal processing method and received-signal processing apparatus for electromagnetic wave probe
WO2002023225A1